SiGeC alloy layer formation by high-dose C+ implantations into pseudomorphic metastable Ge0.08Si0.92 on Si(100) - Im, S; Song, JH; Lie, DYC; Eisen, F; Atwater, H; Nicolet, MA (AMER INST PHYSICS, 1997)
Dual-energy carbon implantation (1X10(16)/cm(2) at 150 and at 220 keV) was performed on 260-nm-thick undoped metastable pseudomorphic Si(100)/Ge0.08Si0.92 with a 450-nm-thick SiO2 capping layer, at either room temperature or at 100 degrees C. After removal of the SiO2 the samples were measured using backscattering/channeling spectrometry and double-crystal x-ray diffractometry. A 150-nm-thick amorphous layer was observed in the room temperature implanted samples, This layer was found to have regrown epitaxially after sequential annealing at 550 degrees C for 2 h plus at 700 degrees C for 30 min, Following this anneal, tensile strain, believed to result from a large fraction of substitutional carbon in the regrown layer, was observed, Compressive strain, that presumably arises from the damaged but nonamorphized portion of the GeSi layer, was also observed. This strain was not significantly affected by the annealing treatment, For the samples implanted at 100 degrees C, in which case no amorphous layer was produced, only compressive strain was observed, For samples implanted at both room temperature and 100 degrees C, the channelled backscattering yield from the Si substrate was the same as that of the virgin sample. (C) 1997 American Institute of Physics.
Keywords: SI1-X-YGEXCY EPITAXIAL LAYERS; STRAIN; GROWTH; SI; COMPENSATION; DAMAGE